Lobbying regulation in V4 countries as an opportunity for elimination of corruption? - Tsurkan, Daniil; Vymětal, Petr; Lisa, Aleš, 1956-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This work provides a comprehensive examination of lobbying regulation within the Višegrad Four countries, aiming to enhance transparency, accountability, and integrity in the decision-making processes. Through a comparative analysis of the existing regulatory frameworks and drawing upon the experiences of countries with advanced lobbying regulations, this study identifies areas for improvement and offers recommendations to strengthen the lobbying legislation in Hungary, the Czech Republic, Slovakia, and Poland. The findings emphasize the significance of robust regulations in eliminating corruption and fostering public trust. By reinstating effective lobbying acts, addressing shortcomings in regulations, learning from international practices, and tailoring approaches to country-specific contexts, these countries can enhance their lobbying regulation and contribute to more effective governance and democratic processes
Vedoucí práce: Petr Vymětal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses